2012
DOI: 10.1007/s10265-012-0508-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses and accumulation of pollutants in woody species under in situ polluted condition in Southern China

Abstract: Physiological leaf traits and accumulation of pollutants of ten woody species in response to air pollution at seriously polluted site Sanguigang (SGG) and control site Maofengshan (MFS) in Southern China were studied. Net photosynthetic rates of most species at SGG were lower than those at MFS, but stomatal conductance (g(s)) showed opposite trend. The specific leaf area of Aporusa dioica, Sapium discolor, Schefflera octophylla and Toxicodendron succedaneum were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Although the mean total Mn concentration in all soils was lower than the background value, both total and extractable soil Mn concentrations were significantly higher in the industrial than in the non-industrial locations (Table 4 and Figure 2), suggesting the possibility of Mn contamination of the soils in the industrial locations. This result was consistent with a previous study in which foliar Mn concentrations for 10 woody species were higher in an industrial location than in a non-industrial location in the study area [20]. Close relationships of soil Mn concentrations with soil Pb and Cu concentrations ( Figure 4 and Table 6) also suggest that soil has been contaminated with Mn in the study area, given that soil Pb and Cu concentrations appear to have been significantly influenced by exogenous sources.…”
Section: Potential Risks Of Heavy Metals In the Soils At Industrial Asupporting
confidence: 92%
See 3 more Smart Citations
“…Although the mean total Mn concentration in all soils was lower than the background value, both total and extractable soil Mn concentrations were significantly higher in the industrial than in the non-industrial locations (Table 4 and Figure 2), suggesting the possibility of Mn contamination of the soils in the industrial locations. This result was consistent with a previous study in which foliar Mn concentrations for 10 woody species were higher in an industrial location than in a non-industrial location in the study area [20]. Close relationships of soil Mn concentrations with soil Pb and Cu concentrations ( Figure 4 and Table 6) also suggest that soil has been contaminated with Mn in the study area, given that soil Pb and Cu concentrations appear to have been significantly influenced by exogenous sources.…”
Section: Potential Risks Of Heavy Metals In the Soils At Industrial Asupporting
confidence: 92%
“…A recent study showed that particulate matter with a diameter <2.5 μm (PM 2.5 ) in the PRD, especially in Foshan, contained >1. For the non-industrial locations, total soil Zn concentrations (121.9-344.4 mg/kg) were markedly higher than the background value for Guangdong Province (47.3 mg/kg) (Table 4), a finding that agrees with previous reports [20,22]. In another previous study, the rate of atmospheric deposition was found to be five to 111 times higher for Zn (3740-6440 ng/m 3 ) than for Cu (34-914 ng/m 3 ) or Pb (147-995 ng/m 3 ) in this area [8].…”
Section: Potential Risks Of Heavy Metals In the Soils At Industrial Asupporting
confidence: 91%
See 2 more Smart Citations
“…So, lower circulating irisin levels have been associated with T2DM. In particular, obese subjects with T2DM present lower irisin levels than non-diabetics, which may contribute to increase IR in this subgroup [191]. One plausible explanation to this fact could be the lower abundance of PGC-1α in skeletal muscle, as patients with early-onset type 2 diabetes display abnormalities in the exercise-dependent pathway that regulates the expression of PGC-1α [192].…”
Section: Irisinmentioning
confidence: 99%